REKAYASA SISTEM MANAJEMEN DALAM PENGENDALIAN MUTU TERPADU - Harimurti, Fadjar (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
ABSTRACT Generally, an integrated quality control is purposed to improve product quality and keep the price clown. An integrated quality system helps the company to give a continuous and integrated concern to the whole companyâ€™s activities. The product quality has been a priority for a company since it supports its development in its productivity. to achieve the purpose of the integrated quality system, an engineering-system approach should lead companies activities for the development and persistence of strong and economically integrated quality control. The modified one will give benefits to the integration of all activities to achieve a policy and quality. Keywords:Â  Management system, quality policy, total quality control